An Integrated Model for Lot Sizing with Supplier Selection Considering Quantity Discounts, Expiry Dates, and Budget Availability - Teguh Ersada Natail Sitepu; Andi Cakravastia (International Journal of Supply Chain Management, 2019)
In this paper, a dynamic multi-product multi-period lot sizing with supplier selection problem (DLSSP) with quantity discount, expiry dates, and budget availability is presented. Demand of products for each period are independent and known. The cost consists of ordering, purchasing, transportation, expiry, holding, and interest charge. The objective is to find the optimal order quantity of all items in each period to minimize inventory cost. A mixed integer nonlinear model programming (MINLP) is first developed to model the problem. Since model is hard to solve using exact method, Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) is applied, in which design parameters are set using Taguchi method. Computational results demonstrate the applicability of the proposed model and comparing the results show efficiency of both algorithms as well. The results show that, while both algorithms have statistically similar performances, GA is the better algorithm in all problems.